Driving Force and Optical Signatures of Bipolaron Formation in Chemically Doped Conjugated Polymers. Issue 3 (9th December 2020) - Voss, Matthew G.; Challa, J. Reddy; Scholes, D. Tyler; Yee, Patrick Y.; Wu, Eric C.; Liu, Xiao; Park, Sanghyun J.; León Ruiz, Omar; Subramaniyan, Selvam; Chen, Mengdan; Jenekhe, Samson A.; Wang, Xiaolin; et al.
Abstract: Molecular dopants are often added to semiconducting polymers to improve electrical conductivity. However, the use of such dopants does not always produce mobile charge carriers. In this work, ultrafast spectroscopy is used to explore the nature of the carriers created following doping of conjugated push–pull polymers with both F4 TCNQ (2, 3, 5, 6‐tetrafluoro‐7, 7, 8, 8‐tetracyanoquinodimethane) and FeCl3 . It is shown that for one particular push–pull material, the charge carriers created by doping are entirely non‐conductive bipolarons and not single polarons, and that transient absorption spectroscopy following excitation in the infrared can readily distinguish the two types of charge carriers. Based on density functional theory calculations and experiments on multiple push–pull conjugated polymers, it is argued that the size of the donor push units determines the relative stabilities of polarons and bipolarons, with larger donor units stabilizing the bipolarons by providing more area for two charges to co‐reside. Abstract : A chemically doped donor–acceptor conjugated polymer is studied using ultrafast spectroscopy, showing conclusively that the carriers created by doping are exclusively bipolarons and not single polarons at all doping levels. DFT calculations show that the physical size of the donor unit is what determines the relative stability of polarons and bipolarons in push–pull semiconducting polymer systems.